Evaluation of phytochemical composition, antioxidant, cytotoxic and in silico studies of ethyl acetate fractions of Tristaniopsis merguensis leaves - Boima Situmeang; Respati Tri Swasono; Tri Joko Raharjo (Toxicology Reports)
Tristaniopsis merguensis is a member of the Myrtaceae family. The leaves of T. merguensis are frequently utilized as herbal tea. The study aimed to evaluate the polyphenolic content, antioxidant, and cytotoxic properties of ethyl acetate fractions derived from Tristaniopsis merguensis (ETM). In addition, it also aimed to conduct an LC-HRMS analysis of a potential fraction to ascertain its suitability as an antioxidant and anticancer active ingredient. An antioxidant evaluation was carried out using the ABTS and DPPH methods. Meanwhile, an in silico study was performed using the target protein elastase (HER-2). A total of twenty metabolites of T. merguensis were identified in the potential fraction ETM.05. In antioxidant testing, the T. merguensis fraction, with code ETM.05, demonstrated potent antioxidant activity based on the ABTS and DPPH methods, with IC50 values of 64.830 ± 2.803 µg/mL and 40.252 ± 0.032 µg/mL, respectively. This resulted in the categorization of the fraction as a strong antioxidant. In the anticancer testing, ETM.05 also demonstrated potent anticancer activity, with an IC50 value of 10.66 µg/mL, which was categorized as a very strong activity in comparison to the positive control (cisplatin), which exhibited an IC50 value of 12.24 µg/mL. The in silico study indicates that the identified metabolites have the potential to bind to the target protein HER-2, which plays a role in remodeling the breast cancer process. This research suggests that the fraction ETM.05 from the ethyl acetate leaves fraction of T. merguensis has the potential to serve as an active antioxidant and anticancer source.